Hegemoni Kekuasaan dalam Naskah Sinrilik I Maddi Daeng Rimakka: Analisis Wacana Kritis Norman Fairclough - Nojeng, Asis; Haliq, Abdul; Ismail, Asri; Basri, Muh. Bahly; Fitriansal, Fitriansal (Nuances of Indonesian Language, 2024)
This research aims to analyze the practice of power domination in the drama script I Maddi Daeng Rimakka through the lens of Norman Fairclough's CDA framework. This research focuses on the potential for domination of power as reflected in the dialogue spoken by I Maddi Daeng Rimakka. This research use desciptive qualitative approach. The data for this research is in the form of conversations that occurred in the manuscript I Maddi Daeng Rimakka. The data source for this research is the drama script I Maddi Daeng Rimakka. The data that has been collected is processed using a qualitative descriptive analysis approach. The data analysis approach goes through the stages of data collection, data reduction, data presentation, and drawing conclusions. The research results reveal that there is a power relationship through the expression I Maddi Daeng Rimakka as a form of representation of the power one has and creates a hierarchical structure.